An experimental study on the cyclic settlement of sand and cemented sand under different inclinations of the bedding angle and loading amplitudes - Al-Rkaby, Alaa; Chegenizadeh, Amin; Nikraz, Hamid (2017)
Although the directional dependence of soil behaviour is a subject of great interest, yet studies of its effects on cyclic settlement are lacking. Therefore, this paper investigated the macro-scale cyclic settlement under various inclinations of bedding plane (a = 0° to 90°) and different loading amplitudes (q c /q u ), and to assess the degree of improvement provided by cement additions which reduce directional dependence. There was high variability in the cyclic settlement of uncemented sand according to bedding plane inclination. The difference between settlement ratios at 0° and 90° were 5.1, 29 and 55% after 100 load cycles with amplitudes of 10, 20 and 30%, respectively. Most of this difference occurred when a = 60°. However, settlement variation became marginal after a large number of load cycles for all amplitudes. Sand treated with cement was improved and it showed a decrease in settlement ratio and elimination of directional dependency. With 7% cement, settlement variation with a did not exceed 12% for all loading amplitudes. However, these effects were still pronounced at lower cement contents, especially when a = 60–90°.